Green manuring: a sustainable approach to restore the soil fertility in shifting cultivation - Kumar, Rakesh; Upadhyay, P. K. (Indian Farming, 2019)
In north-eastern hills region people do not apply chemical fertilizers because of believe that chemical fertilizers are very hazardous to the ecosystem. However, the hilly area soils are not only hungry but thirsty also and this problem is seriously associated with jhum lands. Where organic matter, nutrients and microbial biota is lost due to burning of forests, which leads to heating of the soil. The problem can be mitigated to a great extent by growing green-manuring crops, which will improve the organic matter and micronutrients status of the soil in longer perspectives for sustainable agricultural crop production.